Makna kebenaran dalam epistemologifridrich wilhelm nietzsche - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
, ABSTRACT Truth is a classical problem in Epistemology. This research is titled "The Meaning of Truth in Friedrich Wilhelm Nietzsche's epistemology". It's aim is to expose some problems in Nietzsche's epistemology especially about the truth. The problems in this research are: (1) What truth is in Nietzsche's thought, (2) The relation between truth and "the will to power". This is a library research applying philosophical hermeneutic method. The data are explore from some primary books of Nietzsche's works and some supporting books from commentators or other philosophers. This research used some methodical steps such as: collecting and reading data, then analyzing data with methodical elements: interpretation, deductionindunction, internal coherence, historical continuity, comparison and idealisation. The results of this research are: (1) Truth is not absolute but relative, there is no universal truth. Human's reason doesn't have capability to gain the truth, (2) There is a relation between knowledge or truth and " The Will to Power". The criterion of truth resides in the enhancement of feeling power. Truth is meant to assert life and to increase power.